2018
DOI: 10.1016/j.vaccine.2018.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant live attenuated avian coronavirus vaccines with deletions in the accessory genes 3ab and/or 5ab protect against infectious bronchitis in chickens

Abstract: Avian coronavirus infectious bronchitis virus (IBV) is a respiratory pathogen of chickens, causing severe economic losses in poultry industry worldwide. Live attenuated viruses are widely used in both the broiler and layer industry because of their efficacy and ability to be mass applied. Recently, we established a novel reverse genetics system based on targeted RNA recombination to manipulate the genome of IBV strain H52. Here we explore the possibilities to attenuate IBV in a rational way in order to generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 32 publications
0
32
0
1
Order By: Relevance
“…The viral load of the respiratorytype strain, rH120 in the different tissues indicated that the viral levels in the trachea, early following infection were significantly higher than those of rIBYZ, which indicates that the ability of the virus to attached to trachea epithelial cells of the rH120 strain was stronger than that of the rIBYZ strain. However, during the later time points post-infection, the level of the rH120 strain was significantly lower than rIBYZ, which suggests that the virulence of IBV depends both on tissue invasion and viral replication ability, as well as other functions mediated by other viral proteins (e.g., non-structural, structural, and accessory proteins) [6,29,[58][59][60]. The reduction of the viral load at 5 dpi in the group infected with the rIBYZ strain may be associated with the necrosis and shedding of the trachea epithelium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The viral load of the respiratorytype strain, rH120 in the different tissues indicated that the viral levels in the trachea, early following infection were significantly higher than those of rIBYZ, which indicates that the ability of the virus to attached to trachea epithelial cells of the rH120 strain was stronger than that of the rIBYZ strain. However, during the later time points post-infection, the level of the rH120 strain was significantly lower than rIBYZ, which suggests that the virulence of IBV depends both on tissue invasion and viral replication ability, as well as other functions mediated by other viral proteins (e.g., non-structural, structural, and accessory proteins) [6,29,[58][59][60]. The reduction of the viral load at 5 dpi in the group infected with the rIBYZ strain may be associated with the necrosis and shedding of the trachea epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…In considering the limitations of the live attenuated and inactivated IBV vaccines, reverse genetic IBV vaccines have been developed in recent years as they display increased safety and efficacy [28][29][30]. As reverse genetic technology is primarily based on the H120 and Beaudette strains [31][32][33], both of which are passagegenerated attenuated strains, the mechanism of virus virulence attenuation remains unclear, thereby posing difficulties in the development of attenuated vaccines using this technology.…”
Section: Introductionmentioning
confidence: 99%
“…recombinant viruses. By using reverse genetics, a previous report showed that the replicase gene of IBV is a determinant of pathogenicity (Armesto et al, 2009) and recent studies have shown that IBV pathogenicity is also due to the accessory proteins (Laconi et al, 2018;van Beurden et al, 2018). In order to establish the mechanisms, further study by reverse genetics and animal studies is needed to verify the association between changes in the genome sequence and the pathogenicity of IBV strains.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of S1 sequence analysis might not be solely sufficient to explain the changes observed in IBV antigenicity, tissue tropism, and pathogenicity. In recent years, several studies have noted that viral replication, pathogenicity, and immune escape might be modulated by non-structural and accessory viral proteins in IBV and other coronaviruses (Armesto et al, 2009;Chen et al, 2009;Laconi et al, 2018;Zheng et al, 2008;van Beurden et al, 2018). These findings emphasize the importance of studying the characteristics of the complete genomes of coronaviruses and their associations with antigenicity, tissue tropism, and pathogenicity.…”
Section: Introductionmentioning
confidence: 97%
“…IBV also possesses two accessory genes, Gene 3 and Gene 5, which have been shown to be dispensable for virus replication in cell culture Youn et al, 2005;Hodgson et al, 2006;Bentley et al, 2013). However, it seems that the deletion of accessory genes 3a, 3b, 5a or 5b from IBV could induce an attenuated phenotype both in vitro and in vivo (Laconi et al, 2018;van Beurden et al, 2018).…”
Section: Introductionmentioning
confidence: 99%